THE ROLE OF HISTORICAL AND ARCHAEOLOGICAL MUSEUMS AS SOCIAL INSTITUTIONS IN THE FORMATION AND POPULARIZATION OF HISTORICAL AND CULTURAL MEMORY (ZHOUCOUDIAN MUSEUM, CHINA) - ЛІЗА МАРКІНА (Cхід, 2021)
The article analyzes the role of historical and archaeological museums as public institutions in the formation and promotion of historical and cultural memory in modern conditions of constant change: from the functions of museums through technology to public expectations and needs of the audience. The historical and archaeological museum is considered a socio-cultural institution that fulfills the mission of preserving, broadcasting, and interpreting historical and cultural memory. Based on the properties of historical and cultural memory defined by the author, the functions of museums are established, which ensure its preservation, transition, and interpretation. The article analyzes the dependence of the functions of historical and archaeological museums on changes in the field of communications, technological integration, and the post-epidemic crisis. Given that education and culture are the greatest values of mankind, the author considers one of the main tasks of historical and archaeological museums in the education and cultural de-velopment of society based on historical and cultural heritage. And hence the concept of modern historical and archaeological museums is considered in the direction of scientific and socio-cultural centers.